Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine the other solution to the quadratic equation [tex]\(x^2 + 7x + 12 = 0\)[/tex] given that [tex]\(x = -3\)[/tex] is one of the solutions, we can follow these steps:
1. Understand the structure of the quadratic equation:
A quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex] typically has two solutions. These solutions can be found using factoring or the quadratic formula. Here, our equation is [tex]\(x^2 + 7x + 12 = 0\)[/tex].
2. Recall that [tex]\(x = -3\)[/tex] is a solution:
Since [tex]\(x = -3\)[/tex] is given as one solution, we recognize that [tex]\(-3\)[/tex] satisfies the equation. This means when we substitute [tex]\(-3\)[/tex] back into the equation, it should equal zero.
3. Factor the quadratic equation:
We can factor [tex]\(x^2 + 7x + 12 = 0\)[/tex] to find its roots. The factors of the quadratic equation are typically in the form [tex]\((x - p)(x - q) = 0\)[/tex] where [tex]\(p\)[/tex] and [tex]\(q\)[/tex] are the solutions.
[tex]\[ x^2 + 7x + 12 = (x + 3)(x + 4) \][/tex]
4. Verify the factored form:
By expanding [tex]\((x + 3)(x + 4)\)[/tex], we get:
[tex]\[ (x + 3)(x + 4) = x^2 + 4x + 3x + 12 = x^2 + 7x + 12 \][/tex]
This confirms that the factors are correct.
5. Determine the solutions from the factored form:
Setting each factor equal to zero gives the solutions:
[tex]\[ x + 3 = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
Solving these equations, we get:
[tex]\[ x = -3 \quad \text{or} \quad x = -4 \][/tex]
6. Identify the correct solution from the options:
The given options are:
- (A) -5
- (B) -4
- (C) 1
- (D) 2
- (E) 3
From our factored results, we see that [tex]\(x = -4\)[/tex] is the other solution besides [tex]\(x = -3\)[/tex].
Therefore, the other value of [tex]\( x \)[/tex] is [tex]\(\boxed{-4}\)[/tex].
1. Understand the structure of the quadratic equation:
A quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex] typically has two solutions. These solutions can be found using factoring or the quadratic formula. Here, our equation is [tex]\(x^2 + 7x + 12 = 0\)[/tex].
2. Recall that [tex]\(x = -3\)[/tex] is a solution:
Since [tex]\(x = -3\)[/tex] is given as one solution, we recognize that [tex]\(-3\)[/tex] satisfies the equation. This means when we substitute [tex]\(-3\)[/tex] back into the equation, it should equal zero.
3. Factor the quadratic equation:
We can factor [tex]\(x^2 + 7x + 12 = 0\)[/tex] to find its roots. The factors of the quadratic equation are typically in the form [tex]\((x - p)(x - q) = 0\)[/tex] where [tex]\(p\)[/tex] and [tex]\(q\)[/tex] are the solutions.
[tex]\[ x^2 + 7x + 12 = (x + 3)(x + 4) \][/tex]
4. Verify the factored form:
By expanding [tex]\((x + 3)(x + 4)\)[/tex], we get:
[tex]\[ (x + 3)(x + 4) = x^2 + 4x + 3x + 12 = x^2 + 7x + 12 \][/tex]
This confirms that the factors are correct.
5. Determine the solutions from the factored form:
Setting each factor equal to zero gives the solutions:
[tex]\[ x + 3 = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
Solving these equations, we get:
[tex]\[ x = -3 \quad \text{or} \quad x = -4 \][/tex]
6. Identify the correct solution from the options:
The given options are:
- (A) -5
- (B) -4
- (C) 1
- (D) 2
- (E) 3
From our factored results, we see that [tex]\(x = -4\)[/tex] is the other solution besides [tex]\(x = -3\)[/tex].
Therefore, the other value of [tex]\( x \)[/tex] is [tex]\(\boxed{-4}\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.